Inversi Kuadrat Terkecil Dari Turunan Horizontal Pertama (THP) Anomali Gaya Berat Residual Rata-Rata Berjalan Untuk Menafsirkan Parameter-Parameter Sesar di Segmen Kerinci - Ahmad Fauzi Fauzi; Badrul M. Kemal; W.G.A. Kadir (Institut Teknologi Bandung, 2001)
A quantitative interpretation using a least-squares inverse based on the analytical expression from the first horizontal derivative (FHD) of moving average residual gravity anomalies is used to find depth and thickness of the fault. The problem of the depth determination has been transformed into the problem of finding a solution of a non-linear equation of the form f (z)=0. As a case study, this inverse is applied to carry out the fault parameters in the Kerinci segment. Two lines of gravity survey were carried out along and cross the Sumatra Fault System (SFS). The gravity anomaly pattern reflected a fault structure at northwest Sungaipenuh area in line along SFS and two-fault structure at western and eastern Sungaipenuh area in line cross SFS. The central depth and thickness of fault as a result inverse are 2.533 km and 0.815 km; 1.113 km and 1.985 km; 2.318 km and 4.195 km, respectively, for faults at northwestern, western and eastern Sungaipenuh area. The density contras is assumed - 0,43 g/cm3. Surface layer, basement and the layer faulted are reconstructed with density 2.22 g/cm3, 2.75 g/cm3 and 2.32 g/cm3, respectively. These results inverse agree with 2.5D forward model.